The association between food groups and preeclampsia: a case-control study. (2nd January 2022) - Kooshki, Akram; Sovizi, Behnaz; Mahmoudi, Rahil; Ghezi, Saiedeh; Foroumandi, Elaheh
ABSTRACT: Purpose: The aim of current study was to investigate the correlation between preeclampsia and food groups among pregnant women. Methods: This case-control study was done on pregnant women with a diagnosis of preeclampsia in Sabzevar. The control group was included non-infected postpartum women. Results: Intake of vegetables (OR = 0.952, CI: 0.724–0.985, p < 0.001), fruits (OR = 0.901, CI: 0.852–0.990, p = 0.012), nuts and legumes (OR = 0.712, CI: 0.531–0.848, p = 0.009), and sugars and sweets (OR = 1.254, CI: 1.112–1.497, p < 0.001) were related to the odds of preeclampsia. Conclusions: Women with preeclampsia had lower intake of vegetables, fruits, milk and products, and also fluids. Intake of sugars and sweets compared with the intake of vegetables, fruits, nuts, and legumes was associated with increasing odds of preeclampsia.